2018
DOI: 10.1080/10810730.2018.1473533
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Humor in Messaging about the MMR Vaccine

Abstract: Outbreaks of vaccine-preventable diseases have increased due, in part, to misconceptions about vaccine safety (Kennedy et al., 2011). Extant literature has examined various messages designed to correct false beliefs about vaccination risks and to urge parents to vaccinate their children. The present study is designed to contribute to this literature by drawing on the broader research and theory on resistance to persuasion and correcting false beliefs. We examine the effects of a humorous (vs. non-humorous) mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…Through numerous efforts to erase misconceptions about vaccines and reduce vaccine hesitancy, extant scholarship suggests a few strategies to address the issue. Recent work on messaging about the measles, mumps, and rubella vaccine found that humorous messages “reduced reactance and led to greater perceptions of measles severity” among vaccine-hesitant parents (Moyer- Gusé, Robinson, & McKnight, 2018). In Liberia, the aftermath of the Ebola epidemic exacerbated resistance to childhood vaccinations, leading the government to launch community engagement efforts to dispel myths and misinformation and encourage compliance with childhood vaccines (Bedford et al, 2017).…”
Section: Addressing the Misinformation Epidemic—learning From The Litmentioning
confidence: 99%
“…Through numerous efforts to erase misconceptions about vaccines and reduce vaccine hesitancy, extant scholarship suggests a few strategies to address the issue. Recent work on messaging about the measles, mumps, and rubella vaccine found that humorous messages “reduced reactance and led to greater perceptions of measles severity” among vaccine-hesitant parents (Moyer- Gusé, Robinson, & McKnight, 2018). In Liberia, the aftermath of the Ebola epidemic exacerbated resistance to childhood vaccinations, leading the government to launch community engagement efforts to dispel myths and misinformation and encourage compliance with childhood vaccines (Bedford et al, 2017).…”
Section: Addressing the Misinformation Epidemic—learning From The Litmentioning
confidence: 99%
“…In addition, the topic has received attention in the media, and education about measles and its vaccination is a current topic in health psychology and health communication research (e.g. Camerini et al, 2018; Harvey et al, 2015; Moyer-Gusé et al, 2018). We see MMR as representative of similar medical topics about which patients have some but limited knowledge (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study, which takes this path, examines the reception diff erences in parent audiences confronted with either a Jon Stewart message from the satirical TV series Th e Daily Show, or being presented with a more informative text about the MMR vaccine (Moyer-Gusé et al, 2018). Th ey fi nd that the satirical message reduced psychological reactance and increased the parents' awareness of the seriousness of the diseases being targeted by the vaccine to a larger degree than when presented with the serious text.…”
Section: Related Studiesmentioning
confidence: 99%
“…Even though some recent studies about the use of satire to communicate science in the media have emerged (Feldman, 2017Yeo & Brossard, 2017, they never take on linguistic or stylistic approaches to satire. And rather than being a quantitative study of structuring reception trends as in the above-mentioned study by Moyer-Gusé, Robinson and McKnight (2018), this study will attempt to scrutinise the texture of satirical language and style in order to reach an understanding of the tools needed to maybe alleviate and nuance readers' preexisting ideas and convictions.…”
Section: Related Studiesmentioning
confidence: 99%